Hakikat Manusia Dan Implikasinya Terhadap Pendidikan Dalam Perspektif Islam - Natalia, Sonia; Zahira, Salwa Husna; Gusmaneli, Gusmaneli (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
In Islamic perspective, the essence of human beings encompasses the totality of attributes, essence, and unique characteristics that distinguish them from other creatures. Humans are regarded as honored beings, endowed with intellect and heart, and entrusted with responsibilities as worshippers of Allah (‘abd), stewards on Earth (khalifah), and social beings. The Qur’an describes humans using various terms such as ‘abd Allah, al-Nas, al-Insan, and al-Basyar, each reflecting different dimensions and roles of humanity. This understanding has significant implications for Islamic education, which must emphasize the balance between physical and spiritual aspects. Islamic education should aim to develop human potential holistically through the nurturing of the heart (qalbiyah) and intellect (‘aqliyah), along with the instillation of faith and moral values. The goal is to form a complete human being (insan kamil) capable of fulfilling their role as a khalifah and servant of Allah with balance and responsibility.